Peripheral blood mononuclear cells immunophenotyping in pulmonary tuberculosis patients before and after treatment - Barcelos, Warly; Martins-Filho, Olindo Assis; Guimarães, Tânia Mara Pinto Dabés; Oliveira, Márcio Hamilton Prostzner; Spíndola-de-Miranda, Silvana; Carvalho, Beatriz Nascimento; Toledo, Vicente de Paulo Coelho Peixoto de (Microbiology and immunology, 2006)
Tuberculosis (TB) is a lung disease caused by Mycobacterium tuberculosis. The interaction between the bacillus and the host may lead to a protective cellular immune response. In the present study, we propose the "in vitro" evaluation of this cellular immune response in patients with tuberculosis before and after chemotherapic treatment. Eleven patients with TB and 9 asymptomatic subjects with tuberculin skin test negative (TST-) (purified protein derivative (PPD) <or=10 mm) were evaluated. The peripheral lymphocytes of the subjects were analyzed utilizing the following surface markers: CD3(+), CD4(+), CD8(+), CD19(+), CD25(+), CD56(+), CD14(+), CD16(+) and HLA-DR(+). At the end of the treatment, symptomatic patients presented a significant predominance (P <0.05) of CD4(+) lymphocytes, a significant decrease (P <0.05) in activated CD8(+) T cells and a significant increase (P <0.05) in the marker CD19(+). A predominance of mature NK cells and a significant decrease (P <0.05) in NKT cells were observed. Also observed was a trend toward decrease in immunoregulatory T cells and a predominance of pro-inflammatory macrophages. TST- subjects presented a predominance of CD4(+) over CD8(+) and predominance of CD19(+) and of mature NK cells in comparison to the group of patients, both before and after treatment. Thus, several cell types, such as CD4(+) and CD8(+) T cells, NK cells and their subpopulations, NKT cells and pro-inflammatory macrophages could act in a synergic way to control the growth and multiplication of M. tuberculosis.